2010
DOI: 10.1016/j.red.2010.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Matching frictions, unemployment dynamics and the cost of business cycles

Abstract: We investigate the welfare cost of business cycles implied by matching frictions. First, using the reduced-form of the matching model, we show that job finding rate fluctuations generate intrinsically a non-linear effect on unemployment: positive shocks reduce unemployment less than negative shocks increase it. For the observed process of the job finding rate in the US economy, this intrinsic asymmetry increases average unemployment, which leads to substantial business cycles costs. Moreover, the structural ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 38 publications
(83 reference statements)
5
39
0
1
Order By: Relevance
“…In particular, an increase in the volatility of separations might imply a more efficient reallocation of labour and might be welfare enhancing, rather than welfare reducing. One channel, where an increase in volatility actually has negative effects, is explored in Jung and Kuester (2008) and Hairault et al (2008). These papers show that an increase in the volatilities of the hiring rate might have negative feedback effects on the long-run average turnover rates with associated potential welfare losses.…”
Section: A Normative Perspectivementioning
confidence: 99%
“…In particular, an increase in the volatility of separations might imply a more efficient reallocation of labour and might be welfare enhancing, rather than welfare reducing. One channel, where an increase in volatility actually has negative effects, is explored in Jung and Kuester (2008) and Hairault et al (2008). These papers show that an increase in the volatilities of the hiring rate might have negative feedback effects on the long-run average turnover rates with associated potential welfare losses.…”
Section: A Normative Perspectivementioning
confidence: 99%
“…Finally, Hairault, Langot, and Osotimehin (2010) show that a matching model generates the reduced-form prediction of a positive link between macroeconomic volatility and labor market outcomes. Interestingly, the authors report a negative association between unemployment and total factor productivity, as well as a positive association between unemployment and the squared values of total factor productivity in an annual panel of twenty OECD countries over the period 1982 to 2003.…”
Section: The Review Of Economics and Statisticsmentioning
confidence: 89%
“…In models of unemployment through search and matching frictions,Krause and Lubik (2007),Blanchard and Galì (2010), andHairault et al (2010) have shown that search frictions directly affect the real marginal costs and can contribute to their variation.…”
mentioning
confidence: 99%
“…Following J.-O. Hairault, F. Langot and S. Osotimehin (2010) and also M. Reiter (2012), we set the labour market transition matrices in the economy without business cycles as the equally-weighted average of the transition matrices for booms and recessions in the economy with the aggregate fluctuations. However, the differences across age and skill level are still taken into account.…”
Section: Calculating the Costmentioning
confidence: 99%